An ecological perspective on a river's rights: a recipe for more effective water quality governance?. Issue 6 (3rd October 2019) - Wuijts, Susanne; Beekman, Jappe; van der Wal, Bas; Suykens, Cathy; Driessen, Peter P. J.; Van Rijswick, Helena F. M. W.
ABSTRACT: In several countries, the transfer of legal rights to rivers is being discussed as an approach for more effective water resources management. But what could this transfer mean in terms of a healthy river? We address this question by identifying the ecological requirements for naturally functioning rivers and then explore the demands which these requirements impose on society, the current policy responses to these requirements and whether the transfer of rights to the river could facilitate the preservation of healthy freshwater ecosystems.